El proceso penal frente al estándar denominado «más allá de toda duda razonable»: Un análisis a partir del rol del contador public (2023)
This article expect to clarify the public accountant role inside the penal process, facing the knowledge issue denominated “Beyond all reasonable doubt”, estimate of the penal process for judgement, and the research is focused in the activity like a professional focuses to clarify of the facts. To methodological level, it is a documentary research, with some techniques of critical analysis of the study issue, and finally to collect the information through of the analytical summary, based on the experience. As a final consideration, the study shows that the public accountant has several roles in the penal process, because it can perform like an expert, as a part of penal process, or mediator, and in front of them, the accounting professional will contribute to the supporting evidence, focusing in issues clarifying therefore the International Audit Rules (IAR), take into account techniques, typical of disciplinary field-, that it will serve in the evidence compilation that the penal process requires, for the judge can utter a sentence of the condemnatory position, otherwise absolute. © 2017, Corporacion Universitaria Republicana. All rights reserved.